Dynamic proteome profiling of human pluripotent stem cell-derived pancreatic progenitors. (22nd January 2020) - Loo, Larry Sai Weng; Vethe, Heidrun; Soetedjo, Andreas Alvin Purnomo; Paulo, Joao A.; Jasmen, Joanita; Jackson, Nicholas; Bjørlykke, Yngvild; Valdez, Ivan A.; Vaudel, Marc; Barsnes, Harald; Gygi, Steven P.; Ræder, Helge; et al.
Abstract: A comprehensive characterization of the molecular processes controlling cell fate decisions is essential to derive stable progenitors and terminally differentiated cells that are functional from human pluripotent stem cells (hPSCs). Here, we report the use of quantitative proteomics to describe early proteome adaptations during hPSC differentiation toward pancreatic progenitors. We report that the use of unbiased quantitative proteomics allows the simultaneous profiling of numerous proteins at multiple time points, and is a valuable tool to guide the discovery of signaling events and molecular signatures underlying cellular differentiation. We also monitored the activity level of pathways whose roles are pivotal in the early pancreas differentiation, including the Hippo signaling pathway. The quantitative proteomics data set provides insights into the dynamics of the global proteome during the transition of hPSCs from a pluripotent state toward pancreatic differentiation. : Abstract : Proteome adaptations occur in waves during early stages of human pluripotent stem cell (hPSC) differentiation toward pancreatic progenitors. In this study, we utilized quantitative mass spectrometry-based proteomics, an extremely useful tool, for the discovery of novel molecular signatures of intermediate stages during early pancreatic differentiation. Here, we uncovered a potential regulatory role of the Hippo signaling pathway during hPSC differentiation toward pancreatic progenitors.